Sustainable groundwater governance: India’s challenge and response - Shah, Tushaar (2017)
Since independence, India has emerged as the world’s largest groundwater economy, with annual groundwater use increasing from less than 50 BCM in the 1950s to over 230 BCM today. While this groundwater boom has been the bedrock of India’s agricultural growth, it has also created formidable challenges in groundwater governance. Meeting the challenge of water security in the face of hydro-climatic change requires a paradigm shift in our official thinking about groundwater governance. Although the Central Ground Water Board is the custodian of the nation’s groundwater resource, in reality, multiple agencies in public and private sectors have emerged as major players in India’s groundwater economy. This paper reviews international experience in groundwater governance and argues for greater synergy and coordination among various stakeholders group to improve productivity, equity and ecological sustainability of India’s groundwater economy.